2005
DOI: 10.1038/sj.ejcn.1602350
|View full text |Cite
|
Sign up to set email alerts
|

Oligofructose promotes satiety in healthy human: a pilot study

Abstract: Objective: The administration of a fermentable dietary fibre (oligofructose) in rats increases satietogenic gut peptides and lowered spontaneous energy intake. The aim of the study was to assess the relevance of those effects of oligofructose on satiety and energy intake in humans. Design: Single-blinded, crossover, placebo-controlled design, pilot study. Subjects: Volunteers included five men and five women aged 21-39 years, BMI ranging from 18.5 to 27.4 kg/m 2 , were randomly assigned as described below. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
211
2
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(239 citation statements)
references
References 21 publications
12
211
2
14
Order By: Relevance
“…This merits further investigation. While the doses used in animal studies are not directly transposable to human nutrition, several reports have demonstrated that ingestion of fructo-oligosaccharides at the dose of 5 to 20 g/day are sufficient to promote prebiotic [37][38][39][40] and physiological effects [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…This merits further investigation. While the doses used in animal studies are not directly transposable to human nutrition, several reports have demonstrated that ingestion of fructo-oligosaccharides at the dose of 5 to 20 g/day are sufficient to promote prebiotic [37][38][39][40] and physiological effects [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that fermentation of prebiotics by gut microbiota resulted in reduced hunger and increased satiety, thereby decreasing total energy intake by about 10%. 25,26 Activation of GPR 43 reduces inflammation and stimulates GLP1 and GLP2 release from L cells. 27 Changes in the distribution and localization of Zonula Occludens-1 (ZO-1) and Occludin (2 tight junction proteins) in intestinal tissue are associated with the increased gut permeability occurring in obese and diabetic rodents.…”
Section: Role Of Gut Microbiota In Metabolismmentioning
confidence: 99%
“…Prebiotics may exert a satietogenic effect as demonstrated and confirmed in studies with mice in which the effects of acetate on production of appetite suppression were shown, even in absence of increased levels of GLP-1 and PYY (Frost et al 2014). In humans, the satietogenic effects of prebiotics such as oligofructose have also been shown (Cani et al 2006(Cani et al , 2009a.…”
Section: Prebioticsmentioning
confidence: 77%